The Comparative Law Method and Its Correct Application as a Prerequisite for Obtaining Reliability of Research Results - Szymczak, Iwona (Teka Komisji Prawniczej PAN Oddział w Lublinie, 2022)
Approximation of legal systems serves the achievement of similar economic, social or cultural goals. The comparative method is a tool to achieve such goals. This is why the subject matter of this paper is to present the characteristic features of the legal comparison method and all its stages. Results of research that uses this method aim to formulate de lege ferenda conclusions for the national legislator. The main hypothesis of this article is to demonstrate that the truth of the research result obtained by a comparatist largely depends on the correct application of the comparative method. Nevertheless, it is not the only factor that affects reliability of the research result. The article also points to the relationship of comparative law with neighbouring scientific disciplines and in particular with the theory of law, where this relationship concerns convergence of legislative goals. This is why a lawyer – comparatist, who is preparing a comparative law study, should draw on the research method developed in the theory of legal comparison and on the achievements of the theory of law. The discussion opens with a presentation of a short historical overview of the essence of the dispute on the perception of comparative law either as an independent scientific disciple or as only a specific research method (section 1). When it comes to the characteristics of the comparative law method, its general properties are presented first (section 2), followed by a description of its special features (section 3). It is in particular unique in the fact that it is implemented in stages during which specific activities must be performed. Adherence to this multi-stage procedure is significant in obtaining reliable research results.